2009
DOI: 10.1002/mc.20599
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal destabilization and cathepsin B contributes for cytochrome c release and caspase activation in embelin‐induced apoptosis

Abstract: XIAP is an important antiapoptotic protein capable of conferring resistance to cancer cells. Embelin, the small molecular inhibitor of XIAP, possesses wide spectrum of biological activities with strong inhibition of nuclear factor kappa B and downstream antiapoptotic genes. However, the mechanism of its cell death induction is not known. Our studies using colon cancer cells lacking p53 and Bax suggest that both lysosomes and mitochondria are prominent targets of embelin-induced cell death. Embelin induced cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…LMP, as a distinct event in the apoptotic pathway, is now widely accepted (16,55,56) and is believed by many to occur upstream of mitochondrial outer membrane permeabilization and caspase-3 activation (57,58). This is consistent with our findings, given that LMP was evoked after 6 h of exposure to A␤, whereas DNA fragmentation and caspase-3 activation typically do not occur at a significant level until 48 h post-A␤ treatment.…”
Section: Discussionsupporting
confidence: 91%
“…LMP, as a distinct event in the apoptotic pathway, is now widely accepted (16,55,56) and is believed by many to occur upstream of mitochondrial outer membrane permeabilization and caspase-3 activation (57,58). This is consistent with our findings, given that LMP was evoked after 6 h of exposure to A␤, whereas DNA fragmentation and caspase-3 activation typically do not occur at a significant level until 48 h post-A␤ treatment.…”
Section: Discussionsupporting
confidence: 91%
“…We found that brain glioma cell growth inhibited by embelin was associated with apoptosis. Joy et al (27) found that embelin arrested the cell cycle of colon cancer cells at phase G1 via downregulation of the p21 gene. Our findings are fundamentally identical to theirs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in myeloid leukemia cells, the activation of temperature-sensitive p53 is sufficient to cause LMP that precedes MOMP (Yuan et al, 2002). Furthermore, early LMP in TNF-treated fibrosarcoma cells (Li et al, 2007), embelin-treated colon cancer cells (Joy et al, 2010), as well as in cortical neurons exposed to D9-tetrahydrocannabinol or b-amyloid (Fogarty et al, 2010;Gowran and Campbell, 2008) depends on p53 and is associated with the localization of phospho-Ser15-p53 to the lysosomal membrane. The recruitment of phosphoSer15-p53 to the lysosomes depends on LAPF (LMP-inducing lysosome-associated apoptosis-inducing protein containing PH and FYVE domains) (Li et al, 2007).…”
Section: P53mentioning
confidence: 99%